Identification of two KPC variants, KPC-204 and KPC-227, in ST11-K64 Klebsiella pneumoniae during prolonged hospitalization of a single patient - Sun, Shijun; Zhou, Chaoe; Li, Haijun; Sun, Liying; Qi, Saiqi; Liu, Xinmin; Wang, Wanhai (Frontiers in Microbiology, 2025)
IntroductionCarbapenem-resistant Klebsiella pneumoniae (CRKP) represents a critical global public health challenge due to its significant association with morbidity and mortality. Ceftazidime-avibactam (CZA) has emerged as an effective therapy against CRKP producing the serine carbapenemase KPC; however, resistance driven by novel KPC variants is increasingly reported.MethodsIn this study, 27 CRKP isolates were collected from elderly pneumonia patients in China. Sequential isolates from a single patient undergoing prolonged hospitalization revealed dynamic resistance evolution.ResultsWhole-genome sequencing identified KPC-227, a novel KPC variant, alongside the previously reported KPC-204. KPC-204, carrying a “DDK” insertion at position 270, conferred resistance to both carbapenems and CZA, while KPC-227, harboring a D179Y mutation, restored carbapenem susceptibility but maintained CZA resistance. Molecular docking analyses revealed that the D179Y mutation impaired meropenem hydrolysis by decreasing binding affinity. Additionally, colistin resistance was observed due to a novel mgrB mutation.DiscussionThese findings highlight the high evolutionary potential of KPC enzymes and the importance of vigilance to curb the emergence and dissemination of resistance, which threatens the efficacy of critical lastresort antibiotics.